The Authority Of The House Of Representatives In The Dismissal Of Constitutional Court Judges Based On The Constitution Of The Republic Of Indonesia - Veldrin Pua, Brendah; Neltje Saly, Jeane (UNIVERSITAS PAKUAN, 2022)
This study aims to analyze the authority of the House of Representatives (DPR) regarding the dismissal of Constitutional Court (MK) judges based on the constitution of the Republic of Indonesia. This research focuses on the impeachment mechanism, which is the legal basis for removing Constitutional Court judges who have seriously committed violations. The research method used normative legal research with a document analysis approach. The data consists of the constitution, laws, and regulations related to the House of Representatives authority regarding removing Constitutional Court judges. Data were collected from decisions of the Constitutional Court regarding previous cases involving the dismissal of Constitutional Court judges. The analysis showed that the House of Representatives authority in removing Constitutional Court judges is based on Article 24B Paragraph (2) of the 1945 Constitution of the Republic of Indonesia. House of Representatives has an important role in the impeachment process, where the election of Constitutional Court judges requires the approval of the House of Representatives. In addition, the dismissal of Constitutional Court judges can be carried out by 2/3 of the total House of Representatives members. This research provides a better understanding related to the mechanism of the House of Representatives' authority over the removal of Constitutional Court judges, with a focus on the impeachment process. The implication of this research is the importance of maintaining the independence of the Constitutional Court and ensuring that the impeachment process is carried out fairly based on applicable legal provisions concerning democratic principles and the rule of law. This research contributes to the understanding of the House of Representatives authority in monitoring the powers of the constitutional judiciary. It underlines the importance of maintaining the balance of power within the constitutional system of the Republic of Indonesia